The effect of copper thickness in catalytic converters on HC and CO emissions - Albaihaqi Hilmi; Yuniarto Agus Winoko (Politeknik Negeri Lhokseumawe, 2025)
Advances in transportation technology has significantly increases human mobility and supported economic growth, however it has also led to a rise in harmful exhaust emissions, which adversely affect air quality and contribute to climate change. To address this, it is essential to minimize exhaust emissions, one effective method being the use of catalytic converters. This study aims to investigate the effect of copper thickness, specifically variations of 0.2 mm, 0.5 mm and 0.7 mm as the basic material of catalytic converters. Experimental research using Honda Vario 125 motorized vehicles operating on Pertalite fuel, with emissions measured at varying engine speeds from 1500 rpm to 7000 rpm. The QROTECH QRO 401 gas analyzer was utilized to assess HC and CO exhaust emissions. The results indicate that the thickness of copper used in catalytic converters can effectively reduce CO and HC emissions. Specifically, the sample with a copper thickness of 0.7 mm demonstrated an average CO emission of 0.36% and a standard deviation of 0.0015, while the HC emission produced an average of 112 ppm with a standard deviation of 14.85.